Exploring The Evolution And Impact Of Intellectual Capital On Organizational Performance: A Systematic Review - Tri Wahyudi; Edy Arisondha; Nana Nofianti; Ika Utami Widyaningsih (ICMA Nasional, 2025)
This study systematically reviews the literature on intellectual capital (IC) and its impact on organizational performance, focusing on the interaction between human, structural, and relational capital. The purpose is to synthesize findings from recent studies and understand how these IC dimensions contribute to performance across different industries and regions. A comprehensive search was conducted in Scopus, resulting in 176 studies published between 2019 and 2024. The analysis reveals that human capital is critical for innovation and service quality in service sectors, structural capital enhances innovation in manufacturing, and relational capital drives market adaptation in emerging markets. The study also highlights the increasing role of digital transformation in reshaping IC management and its impact on performance. The findings underscore the need for a context-specific approach to managing IC, tailored to industry and regional characteristics. This review contributes to the understanding of IC’s role in organizational success and offers directions for future research, particularly regarding the integration of digital technologies and non-financial performance indicators.